Hakikat Kemiskinan Menurut Montfort Dan Relevansinya Bagi Kehidupan Umat Katolik Di Indonesia - Yakobus Syukur; Antonius Denny Firmanto (Sekolah Tinggi Teologi Real Batam, 2024)
This research aims to explore the nature of poverty according to Montfort and its relevance to the lives of Catholic communities in Indonesia. Poverty is often associated with living in discomfort, injustice, unhappiness, a life of scarcity, and a lack of material wealth to meet one's needs. This common paradigm needs to be examined more deeply using the surgical tool of the nature or spirituality of poverty according to Montfort. The research employs a literature review methodology. The study reveals that Montfort's spirituality of poverty highlights the ability to fulfill responsibilities and live responsibly, especially by engaging with others and paying attention to the needs of many, particularly those who are poor and marginalized. The use of material wealth is emphasized not for worldly pleasures but as a necessary means to support life. The relevance of Montfort's teachings in the context of how Catholics in Indonesia experience their religious life can be seen in three essential attitudes. Firstly, poverty is considered a means to attain holiness. Secondly, poverty is viewed as an effort in service and solidarity. Thirdly, poverty is seen as a means to guide the community towards the virtues of spiritual life. Keywords: God; Catholic church; poverty; humanit; MontfortAbstrak Penelitian ini bertujuan untuk mengeksplorasi hakikat kemiskinan menurut Montfort dan relevansinya bagi kehidupan umat Katolik Indonesia. Kemiskinan kerapkali diidentikkan dengan hidup dalam ketidakadilan, ketidakbahagiaan, hidup yang serba kekurangan, serta hidup yang tidak berharta (hartanya tidak mencukupi kebutuhannya). Paradigma umum ini perlu dikaji lebih dalam dengan menggunakan pisau bedah hakikat atau spiritualitas kemiskinan menurut Montfort. Penelitian ini menggunakan metode penelitian kepustakaan. Kajian ini menemukan bahwa spiritualitas kemiskinan menurut Montfort menunjukkan kesanggupan untuk menjalankan tugas dan hidup secara bertanggung jawab, terlebih terpanggil untuk terlibat dalam hidup dengan orang lain serta menaruh perhatian kepada kebutuhan banyak orang, khususnya bagi mereka yang miskin dan terlantar serta dalam penggunaan harta benda bukan untuk menjadi kesenangan duniawi melainkan diperlukan untuk menunjang hidup. Relevansi ajaran Montfort dalam konteks bagaimana umat Katolik di Indonesia menghayati kehidupan agamanya dapat dilihat dalam tiga sikap penting. Pertama, kemiskinan merupakan sarana menuju kekudusan. Kedua, kemiskinan adalah upaya pelayanan dan solidaritas. Ketiga, kemiskinan adalah sarana untuk menghantar umat kepada keutamaan hidup rohani.Kata Kunci: Allah; gereja katolik; kemiskinan; manusia; Montfort